2020
DOI: 10.1111/ajsp.12408
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the sociocultural models with cultural experiments: A Polish‒English study on {Request → Compliance} in gender relations

Abstract: The dominant model in cross‐cultural psychology largely disregards culture (Boski, 2018). An alternative theory of sociocultural models (SCMs) has been proposed in this volume. SCMs mould cognitive, affective, and behavioural processes of individual persons, as well as their corrective measures should such processes be sidetracked. Because SCMs are culture‐bound, intercultural contacts are likely to be fraught in misconceptions and conflicts, but they may also give rise to attraction and to culture change. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Indeed, the BYAF technique might rely on subtle or important differences between countries, as some studies on cross-cultural psychology pointed out. For example, Boskł (2020) found that male complied far less to male in Poland, but not in England, based on a sociocultural model. We do not know if the distinction we made was the best possible and we cannot compare countries because, France aside, all the others have experiments from only one study.…”
Section: Culturementioning
confidence: 99%
“…Indeed, the BYAF technique might rely on subtle or important differences between countries, as some studies on cross-cultural psychology pointed out. For example, Boskł (2020) found that male complied far less to male in Poland, but not in England, based on a sociocultural model. We do not know if the distinction we made was the best possible and we cannot compare countries because, France aside, all the others have experiments from only one study.…”
Section: Culturementioning
confidence: 99%
“…In his article “Investigating the Sociocultural Models With Cultural Experiments: A Polish‒English Study on (Request → Compliance) in Gender Relations,” (Boski, 2020) Boski critiques the common cross‐cultural psychological approach to studying culture in which researchers implement questionnaires and their translations, and test their measurement invariance testing (Boski, 2018). As an alternative to this approach, he suggests that researchers use a quasi‐experimental procedure for violating the taken‐for‐granted scripts for dealing with gender roles in response to authority figures’ requests.…”
Section: Contributions To This Issuementioning
confidence: 99%